Effectiveness of Domestic Violence Case Investigation by the PPA Unit of the Ogan Komerung Ulu Police - Pradani, Riri Nabila; Winjaya Laksana, Andri (Jurnal Hukum Khaira Ummah, 2025)
Abstract. Domestic Violence (DV) cases in Indonesia are no longer a problem that must be covered up because everyone has the same rights and status in the eyes of the law. The majority of people in Indonesia are a country that still adheres to Eastern customs that still adhere to Patriarchy. Patriarchal culture positions men as rulers and women as second-class humans who must submit to men. In household life, women in particular are positioned as people who only hold reproductive functions such as getting pregnant, giving birth, and raising children who have been born, and domestic functions, namely matters within the home, therefore women are often perceived as weak creatures who only rely on emotions and feelings so that the output produced is illogical. An example of a case that occurred in 2024 with police report number LP.B/26/II/2024/SPKT dated February 20, 2024, which occurred between a husband and wife with the initials SA (Wife) as the victim and AP (Husband) who was the perpetrator on Jl. R. Suprapto, Kemala Raja Village, Baturaja Timur District, Ogan Komering Ulu Regency with a brief chronology of events, namely on Tuesday, February 13, 2024 at around 00.15 the perpetrator (AP) hit his wife (SA) because it was suspected that his wife received money and kept the money a secret so that AP felt annoyed and suspicious of his wife and kicked SA until she was thrown 3 meters away, in addition AP also slapped SA 3 times and caused bruises on SA's right and left cheeks. This case ended P-21 at the prosecutor's office and the suspect AP was sentenced according to the alleged article given. In addition, there is also LP.B/30/II/2025/SPKT/POLRES OKU dated February 26, 2025 which terminated the investigation (SP 3). The termination of the investigation was carried out because the victim withdrew the report because she wanted to improve her relationship with the perpetrator and have children with the perpetrator.